Use of elimination diet in the treatment of Eosinophilic Esophagitis: a review of the literature (Research, Society and Development, 2021)
Eosinophilic Esophagitis (EEo) is a pathology that has been growing over time. Epidemiologically it occurs variably both geographically and by age groups, with a higher incidence in adults than in children. The symptoms are based on the diagnostic picture combined with some clinical features, and can be confused with gastroesophageal reflux disease (GERD). The present study is an integrative review on dietary modifications in patients with EEo. We selected indexed articles from the last 10 years, available in full in English, Portuguese and Spanish. Data collection occurred in the following databases: Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL), National Library of Medicine (PubMED), Medical Literature Analysis and Retrieval System Online (Medline) and Google Scholar. After applying the exclusion and inclusion criteria, 6 articles were selected for analysis and discussion. From the studies, it was concluded that there was improvement in the clinical picture of the patients studied from the adherence to exclusion diets and empirical elimination diets. Foods such as egg, wheat, gluten and milk were the most influential in the EEo, consequently influencing the symptoms. Therefore, the continuous monitoring and adherence to the recommended diet for patients with EEo is of utmost importance for their treatment and the result of reducing their symptoms.